Poly-Universe game family in preschool and primary school STEAM education - Debrenti, Edith; Bordás, Andrea; Hoffmann, Miklós (Frontiers in Education, 2025)
The Poly-Universe educational game family, a manipulative, colorful geometric educational tool, fosters the development of mathematical, logical and artistic competencies, along with soft skills, by leveraging its unique “scale-shifting” symmetry and a universal color combination system. These features offer broad applicability and hold significant potential for influencing education—particularly in the teaching of mathematical fields, such as geometry and combinatorics, but also arts and further interdisciplinary areas. At its core, the game aims to establish a new visual approach to mathematics education. Due to its intricate design, Poly-Universe transcends the boundaries of a traditional game, blending elements of art and mathematics, and play into a unified educational synergy. In this paper we present the findings of a needs analysis and survey conducted with 101 educators across four European countries related to the potential role of the Poly-Universe tool in preschool and primary education. As revealed, teachers predominantly use manipulatives with children aged 3–10. The results indicated a need for a methodological teaching tool suitable for both kindergarten and lower elementary school settings. No significant gender differences were found in preferences for manipulative tools or in attitudes and abilities related to STEAM education. Educators reported that the use of such facilitates the transition from kindergarten to primary school and that both formal and non-formal educational contexts are equally relevant for this age group. The importance of art in STEAM education was also emphasized, with educators expressing a need for additional practical resources and best practices for the application of manipulatives.